Stress Level of Nurses in Intensive Care Unit - Waladani, Barkah; Khoirin Nida, Ni’matul; Setianingsih, Endah (Prosiding University Research Colloquium, 2022)
Nurses as the front line in the implementation of health services, actions, and nursing care. A nurse has emotional sensitivity in dealing with a situation, condition, and patient situation in the hospital. Behind their roles and duties, it turns out that nurses experience psychological disorders, namely stress. This study was conducted to determine the stress level of nurses in the intensive care unit of RSUD Dr. Soedirman, Kebumen. This study used a descriptive design with a cross-sectional design. Respondents in this study were 35 respondents. The research instrument used a Depression Anxiety Stress Scale 42 questionnaire translated into Indonesian. The analysis used a descriptive test. The results obtained by nurses in the Intensive Care Installation Room, RSUD Dr. Sudirman mostly aged 30 years (60.0%), female (74.3%), undergraduate education (54.3%), working period 5 years (71.4%) and married (85.7%). Sudirman mostly with a moderate level of stress category as many as 14 respondents (40.0%). The conclusion that’s nurses in the intensive care unit experience moderate stress.